Numerical investigation on turbulent forced convection and heat transfer characteristic in spirally semicircle-grooved tube - Promthaisong, Pitak; Boonloi, Amnart; Jedsadaratanachai, Withada (My University, 2016)
Turbulent forced convection and heat transfer structure in the spirally semicircle-grooved tube heat exchanger are numerically examined. The computational problem is solved by finite volume method (FVM) with the SIMPLE algorithm. The influences of groove depth and helical pitch on heat transfer, pressure loss, and thermal performance are investigated for turbulent regime, Re = 5000–20,000. As a result, the swirling flow is found through the test section due to the groove on the tube wall. The flow structure in the spirally semicircle-grooved tube can separate into two types: main and secondary swirling flows. The main swirling flow is found in all cases, while the secondary swirling flow is detected when DR ≥ 0.06. The swirling flow disturbs the thermal boundary layer on the tube wall that is an important reason for heat transfer augmentation. In range studies, the enhancements on heat transfer and friction loss are around 1.16–1.96 and 1.2–10.8 time above the smooth tube, respectively. The optimum thermal performance is around 1.11, which detected at DR = 0.06, PR =1.4,andRe = 5000. The correlations of the Nusselt number and friction factor for the spirally semicircle-grooved tube with PR =1.4 are produced to help to design the tube heat exchanger.
Keywords: Heat transfer; Pressure drop; Spirally semicircle-grooved tube; Turbulent flow